Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Appendix E - Sigma Notation - E Exercises: 48

Answer

$\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}=6-3(\frac{1}{2})^{n-1}$

Work Step by Step

Evaluate $\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}$ $\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}=\frac{3}{2^{0}}+\frac{3}{2^{1}}+\frac{3}{2^{2}}+....+\frac{3}{2^{n}}$ $\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}=\frac{3}{2^{0}}+\sum\limits_{i =1}^{n-1}\frac{3}{2^{i}}$ Here, $\sum\limits_{i =1}^{n-1}\frac{3}{2^{i}}$ shows a geometric series with first term $a=\frac{1}{2}$ and common ratio,$r=\frac{1}{2}$ Therefore, $\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}=3+\frac{\frac{1}{2}(\frac{1}{2}^{n}-1)}{\frac{1}{2}-1}$ $=3+3(1-\frac{1}{2}^{(n-1)})$ $=3+3-3(\frac{1}{2}^{(n-1)})$ Hence, $\sum\limits_{i =1}^{n}\frac{3}{2^{i-1}}=6-3(\frac{1}{2})^{n-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.